Methodological and conseptual difficulties of analysing the working poor population in Europe - Bruder, Emese; Obádovics, Csilla; Meulders, Danièle; O’Dorchai, Síle (REGIONAL AND BUSINESS STUDIES, 2011)
The situation of the working poor received very little attention in Europe until the late ’90s, and very few researchers or governmental organizations considered this issue to be of importance. The existence of the group of people who are working, but remain poor, gained a more prominent place in the European debate after 2000, when the European Union adopted the Lisbon Strategy with a focus on employment, economic, and social policies. A new indicator, the in-work poverty risk has been added to the Laeken indicators in 2003. The European Commission defined in-work poverty as those individuals, who are employed for at least half of the year and have an equalized household income below 60% of the national median income. Since its introduction, this indicator has been amply analyzed and criticized. In this paper our objective is to assess the conceptual and methodological questions and difficulties we faced even at the very beginning of the analysis of the working poor. This concerns conceptual formulation of the notion of the working poor, the whole debate on definitions of worker and poverty used in different analysis, the conflict of combining two levels of analysis, household and individual measures, the assumption of sharing within the household, possibilities of individualizing incomes while looking for statistical data support, weaknesses of the EU-SILC 2007 database concerning the individualized working poverty measure, etc. Keywords: working poor, poverty, inequality